SARS in context : memory, history, policy - Duffin, Jacalyn; Sweetman, Arthur (McGill-Queen's/Associated Medical Services studies in the history of medicine, health, and society ;, 2006)
Less than a year after the SARS outbreak in Toronto and well before the official reports were written, physicians involved in the control of the SARS outbreak joined with several historians of disease and policy experts to reflect on the crisis. The essays in SARS in Context are based on the papers and presentations from the 2004 symposium. Former Ontario Chief Coroner James Young and infectious disease expert Dick Zoutman recount their efforts to contain the mysterious new disease. In answer to questions about "lessons from the past," several distinguished historians of epidemics examine how their knowledge of responses to older plagues influenced their perception of SARS. They also reflect on how the advent of SARS alters their views of the past. Finally, policy experts comment on possible changes to health care that the SARS experience suggests should be made.